COLOR IMAGE COMPRESSION USING DISCRETE COSINUS TRANSFORM (DCT) - Saputra, Adietiya R. (Universitas Gunadarma, 2017)
Multimedia continues to grow. One of the most widely used elements in multimedia is images. An important component of the image is color. In the development of multimedia, color image is more often used because they are more interesting and informative. Along with these developments, a way to store and send images efficiently is required with the color quality of the image is maintained. The purpose of this research is to compress the color in color images so that the image is more efficient in storage, but people can still capture the information provided by that image. In this research 2D-DCT (Discrete Cosine Transform) is used for compressing a color image in order to have less memory but still have a good quality. The result is a compressed image with much smaller size than the source image but does not look much different when viewed by the human eye. The result showed the percentage of compression achieved 95.88 percent for extreme image and achieved 97.59% for the soft color (homogeneous). This technique does not damage the image and has a high compression ratio for lossy compression. Keywords : image compression, DCT, quantization